English Grammar: Understanding, Learning, Developing (Journal of Science-Innovative Research in Uzbekistan, 2023)
English grammar is a fundamental part of language learning. This article will help you understand, learn and develop grammar in English. In the article, the origin of grammar, its historical development and the role of great personalities in the study of grammar are shown.